Structure and Development of Flowers and Inflorescences in Burmannia (Burmanniaceae, Dioscoreales) - Yudina, Sophia V.; Kocyan, Alexander; Truong, Ba Vuong; Vislobokov, Nikolay A.; Lyskov, Dmitry F.; Nuraliev, Maxim S.; Remizowa, Margarita V. (Frontiers in Plant Science, 2022)
Species of the genus Burmannia possess distinctive and highly elaborated flowers with prominent floral tubes that often bear large longitudinal wings. Complicated floral structure of Burmannia hampers understanding its floral evolutionary morphology and biology of the genus. In addition, information on structural features believed to be taxonomically important is lacking for some species. Here we provide an investigation of flowers and inflorescences of Burmannia based on a comprehensive sampling that included eight species with various lifestyles (autotrophic, partially mycoheterotrophic and mycoheterotrophic). We describe the diversity of inflorescence architecture in the genus: a basic (most likely, ancestral) inflorescence type is a thyrsoid comprising two cincinni, which is transformed into a botryoid in some species via reduction of the lateral cymes to single flowers. Burmannia oblonga differs from all the other studied species in having an adaxial (vs. transversal) floral prophyll. For the first time, we describe in detail early floral development in Burmannia. We report presence of the inner tepal lobes in B. oblonga; the growth of the inner tepal lobes is arrested after the middle stage of floral development of this species, and therefore they are undetectable in a mature flower. Floral vasculature in Burmannia varies to reflect the variation of the size of the inner tepal lobes; in B. oblonga with the most reduced inner tepals their vascular supply is completely lost. The gynoecium consists of synascidiate, symplicate and asymplicate zones. The symplicate zone is secondarily trilocular (except for its distal portion in some of the species) without visible traces of postgenital fusion, which prevented earlier researchers to correctly identify the zones within a definitive ovary. The placentas occupy the entire symplicate zone and a short distal portion of the synascidiate zone. Finally, we revealed an unexpected diversity of stamen-style interactions in Burmannia. In all species studied, the stamens are tightly arranged around the common style to occlude the flower entrance. However, in some species the stamens are free from the common style, whereas in the others the stamen connectives are postgenitally fused with the common style, which results in formation of a gynostegium.